Anlotinib Inhibits Cell Proliferation, Migration and Invasion via Suppression of c-Met Pathway and Activation of ERK1/2 Pathway in H446 Cells - Tang, Xiali; Zheng, Ying; Jiao, Demin; Chen, Jun; Liu, Xibang; Xiong, Shan; Chen, Qingyong (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Small Cell Lung Cancer (SCLC) represents the most aggressive pulmonary neoplasm and is often diagnosed at late stage with limited survival, despite combined chemotherapies. The purpose of this study was to investigate the effect of anlotinib on SCLC and the potential molecular mechanisms. Methods: Cell viability was assessed by CCK-8 assay to determine the adequate concentration of anlotinib. Then, effects of anlotinib on cell apoptosis, cell cycle distribution, migration and invasion were analyzed by flow cytometry, PI staining, wound healing assay and transwell assay, respectively. The protein expression of c-met and ERK1/2 pathways in H446 cells were assessed by western blot analysis. Results: In this study, we found that anlotinib significantly reduced the cell viability of H446 cells, induced G2/M cell cycle arrest and decreased invasion and migration of H446 cells. Futhermore, we also found that anlotinib could suppress c-met signal transduction and activate the ERK1/2 pathway in H446 cells. More importantly, c-met was involved in the effects of anlotinib on migration and invasion in H446 cells. Conclusion: Taken together, our results demonstrated that anlotinib was a potential anticancer agent that inhibited cell proliferation, migration and invasion via suppression of the c-met pathway and activation of the ERK1/2 pathway in H446 cells.
Keywords: small cell lung cancer